2016
DOI: 10.1016/j.ipej.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy prevents progression of renal failure in heart failure patients

Abstract: BackgroundThe goal of this study is to assess the effect of cardiac resynchronization therapy (CRT) over time on renal function and its impact on mortality. The effect of CRT on renal function in patients with heart failure is not well understood.MethodsAll patients who underwent CRT implantation at University of Kansas between year 2000 and 2009 were reviewed and patients who had pre and post CRT renal function studied were included in our study. Stages of chronic kidney disease (CKD) were defined based on Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…There is no broad consensus of the relative effectiveness of CRT-D over CRT-P, and therefore studies looking at the all-cause death rate and HF death rate could prove to be important in reducing the uncertainty around cost-effectiveness results. In addition, given the high proportion of eligible patients not responding to CRT [7] or not needing the addition of an ICD [5], future studies need to better identify CRT-P patients that will have a reasonable life expectancy when treated with CRT-D. This would bring down avoidable costs, and consequently improve cost-effectiveness of CRT-D over CRT-P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no broad consensus of the relative effectiveness of CRT-D over CRT-P, and therefore studies looking at the all-cause death rate and HF death rate could prove to be important in reducing the uncertainty around cost-effectiveness results. In addition, given the high proportion of eligible patients not responding to CRT [7] or not needing the addition of an ICD [5], future studies need to better identify CRT-P patients that will have a reasonable life expectancy when treated with CRT-D. This would bring down avoidable costs, and consequently improve cost-effectiveness of CRT-D over CRT-P.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of an implantable cardioverter defibrillator to the resynchronization therapy (CRT-D) can further reduce the risk of death from any cause by more than 8 % (compared to CRT-P) [3], while the risk of sudden death (SCD) can be reduced by 23 % [46]. However, overall costs of CRT-D are high and it is reported that about 25 to 35 % of the patients do not respond to CRT-P [7] while implantable cardioverter defibrillators (ICDs) are not always needed to deliver the therapy [5]. …”
Section: Introductionmentioning
confidence: 99%
“…CRT response is associated with the stabilization or improvement of renal function, which, in turn, is associated with lower mortality [52, 53]. A meta-analysis suggested that diabetic patients with advanced HF who received CRT exhibited higher total mortality than nondiabetic patients [54].…”
Section: Noncardiac Comorbiditiesmentioning
confidence: 99%
“…present data from a single center (University of Kansas Medical Center, MO, USA) on the effect of CRT on renal function [10]. In a cohort of 558 patients who underwent CRT implants at their institution, 80% has mild renal dysfunction (Stage 2 or 3) at baseline.…”
mentioning
confidence: 99%
“…Transvenous techniques run the risk of worsening renal function with the use of radiographic contrast used to define coronary sinus anatomy. In the present study [10], the operators used minimal contrast (40–45 cc) to minimize renal damage and utilized hydration and sodium bicarbonate over the 24-hour period around the implantation. Other than maintenance of adequate hydration and maintaining adequate urine flow in the post exposure period, it is unclear whether any other pre-treatment alters the risk of contrast nephropathy.…”
mentioning
confidence: 99%